ANALISIS NILAI TAMBAH DAN KELAYAKAN PENGEMBANGAN AGROINDUSTRI BERAS SIGER - Wike Novia; Wan Abbas Zakaria; Dyah Aring Hepiana Lestari (Lampung University, 2013)
The purposes of this research are to analyze the added value and the feasibility of ‘siger’ rice agroindustry development. ‘Siger’ rice is rice that made of cassava in the form of granules such as rice. This research uses a case study method on SU (a micro enterprise)’s siger rice agroindustry at Pinang Jaya village of Kemiling Disrict of Bandar Lampung City and SS (a small enterprise)’s siger rice agroindustry at Pancasila Village of Natar District of South Lampung Regency. The research location was chosen purposively based on the quantity of workers. The data was analyzed by quantitative and descriptive qualitative. The results of this research showed that SU’s siger rice agroindustry gave an added value of Rp3,065.38 per kg of raw materials (2.04 times of its price). Meanwhile, SS’s siger rice agroindustry gave an added value of Rp1,508.04/kg of raw materials (1.68 times of its price). The agroindustry of SU’s and SS’s siger rice were profitable and feasible to be developed; however there were problems in marketing and production technology usage so that those capacities could not be increased yet. Keywords: added value, agroindustry, feasibility, siger rice